Unraveling of Diagnosis Odyssey in A Girl with Primary Amenorrhea: A case report - Ni Made Indri Dwi Susanti; Inu Mulyantoro; Dik Puspasari; Nurin Aisyiyah Listyasari; Sultana MH Faradz (Faculty of Medicine, Diponegoro University, 2020)
ABSTRACT Background:Primary amenorrhea may result from congenital abnormalities in the development of the gonads, genital tract, or external genitalia or from a disturbance within the hypothalamic-pituitary-ovarian axis. Gonadal dysgenesis is a disorder of sex development in which the diagnosis is based on the histology of gonads and is the main cause of primary amenorrhea. Optimal protocol of management for phenotypic female with 46, XY gonadal dysgenesis involves prophylactic gonadectomy at diagnosis.Case Presentation: The patient was referred to our hospital at the age of 15 years old for primary amenorrhea. She was obese with no secondary sex sign. Gynecologic examination revealed a normal vagina and clitoris. Rectal Toucher examination revealed no internal genitalia structure. The laboratory data: FSH levels was above normal range, LH and testosterone levels were within normal range. Pelvic Ultrasonography uterus and vaginal structure and testis were not visualized. Cytogenetic and ARgene analysis found a 46, XY karyotype and no pathogenic variants. On laparoscopy, Mullerian structure and Wolffian remnant structure were identified and biopsies were performed. Based on histopathological examination and immunohistochemical markers of the right and left gonad showed the impression of Malignant Mixed Germ Cell-Sex Cord Stromal Tumor. SRY gene examination was positive.Examination of other DSD gene analysis has not been done. Second laparoscopy for gonadectomy and removal of Mullerian and Wolfiian remnant structure were performed. Conclusion:Chromosomal analysis should become the first line testing in primary amenorrhea followed by advanced molecular test. Multidisciplinary managements recommended for DSD cases.